Participatory groundwater management at village level in India – empowering communities with science for effective decision making - Jadeja, Y.; Maheshwari, B.; Packham, R.; Hakimuddin; Purohit, R.; Thaker, B.; Goradiya, V.; Oza, S.; Dave, S.; Soni, P.; Dashora, Y.; Dashora, R.; et al. (2015)
There are many reasons behind the worsening groundwater situation that have led to a scarcity of quality water supply for sustaining lives and livelihoods in India, as well as in other parts of the world. The lack of a proper scientific understanding of this situation by the various stakeholders has been identified as one of the important gaps in the sustainable management of groundwater. This paper shares experiences from Gujarat and Rajasthan in western India where scientists, NGOs, government agencies and village leaders have worked together to explore strategies for sustainable groundwater management. The study involved a total of eleven villages in Gujarat and Rajasthan, India. The study’s main aim was to educate these communities through an intensive capacity building of (mainly) rural youth, called Bhujal Jaankars (BJs), a Hindi word meaning ‘groundwater informed’. The BJs were trained in their local settings through relevant theory and practical exercises, so that they could perform a geo-hydrological evaluation of their area, monitor groundwater and share their findings and experiences with their village community. The BJs went through a training program of a series of sessions totalling 45-days that covered mapping, land and water resource analysis, geo-hydrology, and water balance analysis, and finally groundwater management strategies. This approach has highlighted important learning that can be replicated in other parts of the two states and beyond. There are now 35 trained BJs who regularly monitor groundwater and rainfall in the two study watersheds, and provide data to both scientific and their own rural communities. This study has demonstrated that BJ capacity building has helped to provide a scientific basis for village level groundwater dialogue. This is now leading the communities and other stakeholders to improve their decision making regarding groundwater use, crop selection, agronomy, recharge strategies and other aspects of sustainable groundwater management. Although the BJ program has been successful and BJs can act as a valuable interface between local communities and other stakeholders, there still exists some challenges to the BJ programme, such as the need for mechanisms and funding sources that will sustain the BJs over the longer term; wider acceptance of BJs among scientific communities and policy makers; and the acceptance of the role and involvements of BJs in natural resources management programs of the State and Central governments in India.